PRODUCTIVE RESPONSE AND PROGESTERONE CONCENTRATION IN HOLSTEIN HEIFERS SUPPLEMENTED WITH SACCHAROMYCES CEREVISIAE1077 OR SACCHAROMYCES BOULARDII1079 - U. Coronel-Robles; M.E. Ortega-Cerrilla; G.D. Mendoza-Martínez; P. Zetina-Córdoba; M.T.S. Torres-Esqueda; G. Munguía-Ameca; M.V. Teco-Jácome (Journal of Animal and Plant Sciences, 2016)
The objective of this study was to determine the effect of supplementating 10 g/animal/day of Saccharomyces cerevisiae1077 (SC1077) or Saccharomyces boulardii1079(SB1079) on dry matter intake (DMI), daily weight gain (DWG), feed efficiency (F:G), in vivo digestibility, pH, and rumen ammonia nitrogen (NH3-N) concentration in rumen liquor, as well as progesterone concentration (P4). Twenty four, six-month old, Holstein heifers were randomly assigned to three treatments (n=8): (T1: Control; T2:10 g/animal/day of SC1077; T3:10 g/animal/day of SB1079). Samples of rumen liquor were taken at 60, 120 and 180 d of the experiment to determine pH and ammonia nitrogen. Determination of in vivo digestibility of DM, NDF, ADF and N was carried out 14 days before the of 60, 120, and 180 d periods. Blood samples were taken to measure P4 concentration. No differences (P > 0.05) were found for DMI, DWG, and F:G from supplementing with S. cerevisiae. Similarly, no differences were reported for rumen pH and rumen NH3-N concentration were not affected (P > 0.05), and in vivo digestibility of DM, NDF, ADF and N (P > 0.05). The P4 concentration was similar (P > 0.05) among the treatments. It is concluded that supplementing Holstein heifers with SC1077 and SB1079 did not improve heifers performance nor modified the progesterone concentration.
Keywords: Saccharomyces; replacement heifers; digestibility